AcanR3990 qPCR: A Novel, Highly Sensitive, Bioinformatically-Informed Assay to Detect Angiostrongylus cantonensis Infections - Sears, William J; Qvarnstrom, Yvonne; Dahlstrom, Eric; Snook, Kirsten; Kaluna, Lisa; Baláž, Vojtech; Feckova, Barbora; Šlapeta, Jan; Modry, David; Jarvi, Susan; Nutman, Thomas B (Clinical infectious diseases, 2021)
BACKGROUND: Angiostrongylus cantonensis (Ac), or the rat lungworm, is a major cause of eosinophilic meningitis. Humans are infected by ingesting the 3rd stage larvae from primary hosts, snails, and slugs, or paratenic hosts. The currently used molecular test is a qPCR assay targeting the ITS1 rDNA region (ITS1) of Ac. METHODS: In silico design of a more sensitive qPCR assay was performed based on tandem repeats predicted to be the most abundant by the RepeatExplorer algorithm. Genomic DNA (gDNA) of Ac were used to determine the analytical sensitivity and specificity of the best primer/probe combination. This assay was then applied to clinical and environmental samples. RESULTS: The limit of detection of the best performing assay, AcanR3990, was 1 fg (the DNA equivalent of 1/100 000 dilution of a single 3rd stage larvae). Out of 127 CDC archived CSF samples from varied geographic locations, the AcanR3990 qPCR detected the presence of Ac in 49/49 ITS1 confirmed angiostrongyliasis patients, along with 15/73 samples previously negative by ITS1 qPCR despite strong clinical suspicion for angiostrongyliasis. Intermediate hosts (gastropods) and an accidental host, a symptomatic horse, were also tested with similar improvement in detection observed. AcanR3990 qPCR did not cross-react in 5 CSF from patients with proven neurocysticercosis, toxocariasis, gnathostomiasis, and baylisascariasis. AcanR3990 qPCR failed to amplify genomic DNA from the other related Angiostrongylus species tested except for Angiostrongylus mackerrasae (Am), a neurotropic species limited to Australia that would be expected to present with a clinical syndrome indistinguishable from Ac. CONCLUSION: These results suggest AcanR3990 qPCR assay is highly sensitive and specific with potential wide applicability as a One Health detection method for Ac and Am.
Keywords: Strongylida Infections; krysa rodu Rattus; Animals; Angiostrongylus cantonensis; Horses; Humans; lidé; infekce hlísticemi řádu Strongylida; zvířata; meningitida; Meningitis; Rats; Angiostrongylus; koně